2017
DOI: 10.1021/acs.jctc.6b01206
|View full text |Cite
|
Sign up to set email alerts
|

Development of the ABEEMσπ Polarization Force Field for Base Pairs with Amino Acid Residue Complexes

Abstract: DNA damage caused by oxidized bases can lead to aging and cancer in living beings. Luckily, a repair enzyme is able to repair the oxidized bases. The key step is to accurately recognize the oxidized bases, which mainly rely on complex hydrogen bond interactions. We have calibrated the charge parameters and torsional parameters of the ABEEMσπ polarization force field (ABEEMσπ PFF) to accurately describe the intermolecular and intramolecular interactions. Taking the experiment and quantum chemical method as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 87 publications
0
35
0
Order By: Relevance
“…Wilson and Ichikawa and Torrent‐Sucarrat and coworkers pointed out that the charge transfer between atoms in a molecule is overestimated by using the polarization basis sets. Huzinaka et al, Jakalian et al, Watanabe et al, and our group have shown that the use of higher levels of basis sets overestimates the overlap between their respective basis functions belonging to two atoms in a molecule. Bayly and his coworkers pointed out that when the 6‐31G* basis set is used, the polarity of a molecule calculated by the partial charges is overestimated by 10%–15% .…”
Section: Computational Detailsmentioning
confidence: 66%
“…Wilson and Ichikawa and Torrent‐Sucarrat and coworkers pointed out that the charge transfer between atoms in a molecule is overestimated by using the polarization basis sets. Huzinaka et al, Jakalian et al, Watanabe et al, and our group have shown that the use of higher levels of basis sets overestimates the overlap between their respective basis functions belonging to two atoms in a molecule. Bayly and his coworkers pointed out that when the 6‐31G* basis set is used, the polarity of a molecule calculated by the partial charges is overestimated by 10%–15% .…”
Section: Computational Detailsmentioning
confidence: 66%
“…Based on the DFT and electronegativity equalization method (EEM) [28][29][30][31][32][33][34] , Yang and his coworkers have developed ABEEM model [35][36][37][38][39][40][41][42][43][44][45] , which explicitly partitions a molecule into atom, chemical bond, and lone pair (lp) regions. In this model, the single bond consists of one  region, where the center of the charge for  bond is located on the position of the ratio of the covalent atomic radii of two bonded atom; the double bond consists of one  region and four π regions, where center of the  bond charge is similar with the σ region of single bond and the  bond partial charges are placed above and below the double-bonded atoms at the covalent radii of the this double-bonded atoms perpendicular to the plane formed by the  bond; and the center of charge and its orientation for the lp region is determined in terms of the chemical surrounding.…”
Section: Abeemσπ Modelmentioning
confidence: 99%
“…a and b denote two regions, including the atom or single bond  or double bond  and  or lone pairs regions. qa and qb are the partial charges of regions a and b, Ra,b denotes the distance between regions a and b, and k, 0.57, is an overall correction coefficient in this formalism 22,[35][36][37][38][39][40][41][42][43][44][45][46][47] . The electronegativity equalization principle demands that the effective electronegativity of every region is equal to the overall electronegativity of the molecule, χmol:…”
Section: Abeemσπ Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Atomic charges of this type are based on the concept of electronegativity. Some methods based on the electronegativity equalization principle in DFT have been developed, such as Mortier's electronegativity equalization method (EEM); the split charge equilibration (SQE) model; Rappé and Goddard's QEq; York and Yang's chemical potential equilibration (CPE); the partial equalization of orbital electronegativity proposed by Gasteiger et al and Scheraga and coworker; the methods proposed by Mullay and Abraham and coworkers; and Yang's atom‐bond electronegativity equalization method (ABEEM), among others …”
Section: Introductionmentioning
confidence: 99%